ANALISIS PENERAPAN PERMENDAGRI 25/2009 DAN ANGGARAN PELAYANAN PUBLIK PADA ANGGARAN PENDAPATAN DAN BELANJA DAERAH PEMERINTAH KABUPATEN MAROS TAHUN ANGGARAN 2010 - Sylvia Sylvia (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
Each entered the new fiscal year, the government issued guidelines for the budget process is to convey the direction of government policy for the new budget year. For fiscal year 2010, the budget process is guided by the Permendagri 25/2009. In this Permendagri 25/2009 Government directed to pay attention to the public with better service. Implementation is realized by allocating a portion of direct expenditure budget that is greater than the indirect spending, and capital expenditures are greater than the expenditures of goods and services and personnel expenditure. After testing, the obtained results that direct expenditure on the Maros district budget in 2010 was not significantly greater than the indirect spending. Then, capital expenditures are budgeted by the District Government in the 2010 budget Maros significantly greater than the share of personnel expenditure while capital expenditure allocation is significantly greater than the expenditures for goods and services. As for public services, there was no significant difference between the budgets of public services is budgeted by SKPD who run the affairs of compulsory and option affairs.